Initiating the Hybrid Teaching Mode of BOPPPR in L2 English Writing Instruction - Min, Lei (Journal of Educational Research and Policies, 2025)
Based on the BOPPPS framework and in accordance with national teaching standards for English majors, this study proposes an innovative BOPPPR teaching model for hybrid second-language English writing instruction. This model emphasizes moral cultivation, digital empowerment, and learning diagnostics. The results demonstrate that the BOPPPR model effectively supports individualized instruction, enhances students’ pragmatic competencies, including syntactic control and discourse organization and develops higher-order cognitive skills such as generalization, analytical thinking, and critical evaluation. Moreover, it fosters disciplined writing habits and promotes collaborative learning literacy. By seamlessly integrating socialist core values, the model also facilitates holistic education. The primary theoretical contributions of this research are twofold: it extends the original BOPPPS framework both theoretically and practically, and introduces the digitally enriched BOPPPR paradigm for whole-person development. These outcomes offer a valuable reference for the design and implementation of first-class courses in the new era.